MORAL INJURY*. Issue 4 (December 2017) - Antonelli, Mildred
Abstract The devastating effect on the self of moral injury, often a core component of trauma, occurring when one's actions have profoundly violated one's code of ethics, when one has been a victim of such violation, or when one has been a passive witness, has been extensively explored as it has occurred in veterans of the wars in Vietnam, Iraq and Afghanistan. Two examples illustrate its prevalence in civilian life. The literature shows violation of expected empathy from and for others, inherent in our nature, is more devastating than violation of the ethical code of our culture or sub-culture, adherence to which becomes urgent as our need emerges to belong to the culture or subculture of which we are a part, values which often contradict our innate sense of "what is right."